The effect of the GLP‐1 analogue Exenatide on functional connectivity within an NTS‐based network in women with and without obesity. (10th November 2017) - Coveleskie, K.; Kilpatrick, L. A.; Gupta, A.; Stains, J.; Connolly, L.; Labus, J. S.; Sanmiguel, C.; Mayer, E. A.
Summary: Objective: The differential effect of GLP‐1 agonist Exenatide on functional connectivity of the nucleus tractus solitaries (NTS), a key region associated with homeostasis, and on appetite‐related behaviours was investigated in women with normal weight compared with women with obesity. Methods: Following an 8‐h fast, 19 female subjects (11 lean, 8 obese) participated in a 2‐d double blind crossover study. Subjects underwent functional magnetic resonance imaging at fast and 30‐min post subcutaneous injection of 5 μg of Exenatide or placebo. Functional connectivity was examined with the NTS. Drug‐induced functional connectivity changes within and between groups and correlations with appetite measures were examined in a region of interest approach focusing on the thalamus and hypothalamus. Results: Women with obesity reported less hunger after drug injection. Exenatide administration increased functional connectivity of the left NTS with the left thalamus and hypothalamus in the obese group only and increased the correlation between NTS functional connectivity and hunger scores in all subjects, but more so in the obese. Conclusions: Obesity can impact the effects of Exenatide on brain connectivity, specifically in the NTS and is linked to changes in appetite control. This has implications for the use of GLP‐1 analogues in therapeutic interventions.